Brazilian psychiatrists approaches on trance and possession phenomena - Almeida, Angélica A. Silva de (2007)
BACKGROUND: Trance and possession experiences have raised interest among Brazilian psychiatrists resulting in a variety of approaches. OBJECTIVES: To describe and analyze how Brazilian psychiatrists approached trance and possession experiences: these experiences impact on theory, research and clinical practice between 1900 and 1950. METHOD: Analysis of papers, thesis, and books on trances and possessions written by Brazilian psychiatrists between 1900 and 1950. RESULTS: We detected two main approaches, the first one, related to schools of medicine in Rio de Janeiro and São Paulo, under strong influence of French researchers, focused on the dangers of spiritism to mental health. They advocated a repressive action to be enforced by governmental authorities. Psychiatrists from schools of medicine in Bahia and Pernambuco formed the second group. Although having not denied the "primitive" or pathological nature of trance and possession phenomena, they held a more anthropological and cultural approach. Some psychiatrists considered these experiences as racial or cultural manifestations, and claimed that the education and medical control of people would make them give up these primitive practices. Others have not considered that mediumistic phenoma are related to mental disorders or inferior cultural level. DISCUSSION: Mediumistic religions were the subject of a long-term investigation conducted by Brazilian psychiatrists resulting in diversified theories and practices which represent a valuable opportunity for the study of sociocultural factors impact on the psychiatric activity.